Assessing Land Use Intensity and Ecosystem Service Dynamics in Citarum Watershed, Indonesia - Irmadi Nahib; Widiatmaka Widiatmaka; Suria Darma Tarigan; Wiwin Ambarwulam; Fadhlullah Ramadhani (Universitas Sebelas Maret, 2025)
Changes in land use and land cover (LULC) significantly impact ecosystem services (ES), often leading to land degradation and disrupting natural balance. This study examines how LULC changes have influenced total ecosystem services (TES) in Citarum Watershed over the past decade. Specifically, researchers analyze (1) the shifts in LULC and key ES components—water yield (WY), soil conservation (SC), and carbon storage (CS)—from 2010 to 2020, (2) the spatial relationship between land use intensity (LUI) and ES, and (3) the synchronization and distribution patterns of LUI and TES using a coupling coordination degree (CCD) model. The findings reveal significant LULC changes between 2010 and 2020, with bare/shrubland and agricultural areas expanding by 88.37% and 2.25%, while forest land and lakes declined by 0.78% and 0.09%. These transformations affected ES values, as WY and CS decreased by 15.01% and 4.98%, whereas SC increased by 12.03%. Overall, TES declined by 7.54%, with the steepest reduction (17.70%) observed in the downstream region. The coupling coordination analysis highlights an imbalance between LUI and TES, with 65 to 68% of sub-districts classified as imbalanced. These results underscore the urgent need for integrated land-use planning strategies to restore ecosystem balance and promote sustainability in Citarum Watershed.